2018
DOI: 10.1016/j.acra.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Communication Practices of Mammography Facilities and Timely Follow-up of a Screening Mammogram with a BI-RADS 0 Assessment

Abstract: Our findings support the value of telephone communication to patients in relation to timely follow-up. Future research is needed to evaluate the role of communication in completing the breast cancer screening episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…20 The quest for efficiency affects key patient outcomes: receiving mammography results by letter vs telephone is associated with decreased understanding, increased frustration and distress, and delayed followup. [21][22][23][24] Many patients in our study reported they did not understand medical jargon in letters and were left uncertain about the meaning of their results, a particular concern for vulnerable patients with low health literacy or limited English proficiency. [24][25][26] Patients were frustrated by the inability to immediately clarify with their clinician the likelihood of cancer and did not like having the onus put on them to call with questions.…”
Section: Discussion and Interpretationmentioning
confidence: 83%
“…20 The quest for efficiency affects key patient outcomes: receiving mammography results by letter vs telephone is associated with decreased understanding, increased frustration and distress, and delayed followup. [21][22][23][24] Many patients in our study reported they did not understand medical jargon in letters and were left uncertain about the meaning of their results, a particular concern for vulnerable patients with low health literacy or limited English proficiency. [24][25][26] Patients were frustrated by the inability to immediately clarify with their clinician the likelihood of cancer and did not like having the onus put on them to call with questions.…”
Section: Discussion and Interpretationmentioning
confidence: 83%
“…19 Patients in facilities that used electronic medical records to notify patients for follow-up were also more likely to experience delay compared with those who received results via telephone. 20 Interventions to address communication barriers will need to focus on providers and healthcare facilities to improve follow-up rates. 21 Recommendations for abnormal test result communication include clearly defining timely follow-up, outlining provider responsibility to communicate results, having fail-safe procedures to ensure delivery, and specifying preferred mechanism of patient notification for critical tests.…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrates the need to assess processes of care at the facility level that may be contributing to timely or delayed follow‐up. While one study has demonstrated a relationship between communication processes and timeliness of follow‐up after an indeterminate mammogram result (Breast Imaging‐Reporting and Data System—BI‐RADS—0), no studies have investigated facility processes of care for more concerning BI‐RADS 4 or 5 results and follow‐up, or their relationship to disparities in follow‐up.…”
Section: Introductionmentioning
confidence: 99%